Strategi pemasaran melalui optimalisasi kualitas layanan untuk meningkatkan kepuasan nasabah bank - Nurfadillah, Viona Anggraini (Maliki Interdisciplinary Journal, 2025)
Intense competition among banks in the world means banks are increasingly competing in providing their services. The aim of this research is to determine the indicators for optimizing service quality that banks must carry out so that customer satisfaction increases. This research uses qualitative research with a literature study approach to produce conclusions from the topics discussed. The results of this research found seven indicators of optimizing service quality, namely improving physical facilities, reliability, communication capabilities, speed of service, complaint handling, credibility and security. Customer satisfaction can be improved or maintained by providing quality services so that customers are not disappointed. Optimization is needed in service quality in order to meet customer expectations. Optimization can be done by improving physical facilities, reliability, communication capabilities, service speed, complaint handling, credibility and service security.